The role of evaluation in avoiding the mistakes of science learners for the eighth grade in some schools of Lattakia (Journal of Hama University, 2022)
The current research aims to know the role of evaluation in avoiding the mistakes of science learners for the eighth grade in some schools in Lattakia, and by applying the questionnaire to a sample of science teachers in Lattakia consisting of (40) teachers and schools, and a questionnaire consisting of (25) items was used. . The results showed:There are statistically significant differences between the average scores of the groups and the differences were in favor of the group with the highest academic qualification, i.e. in favor of (postgraduate studies) compared to the rest of the groups, and in favor of the (diploma) group compared to the group (university degree).There were statistically significant differences between the average scores of the groups, and the differences were in favor of the group with the most years of experience, i.e. in favor of (more than 10 years) compared to the rest of the groups, and in favor of a group (5-10 years) compared to a group (less than 5 years).There is a statistically significant difference between the mean scores of the teachers in the sample members on the questionnaire according to the variable of training courses, and the difference was in favor of the followers of the training courses.
Keywords: calendar, avoiding errors